IMPLEMENTASI PAKTA GLASGLOW DALAM MENANGGULANGI PERUBAHAN IKLIM DI INDONESIA - Risnawaty Juniaty; Khoirunnisa (Pojok Publisher, 2024)
This research evaluates Indonesia's implementation of the Glasgow Pact in the face of climate change. The main focus is on how Indonesia implements this international commitment, using the theories of international cooperation and international regimes as theoretical basis. Qualitative methods were used by analyzing journals, government policies, official reports, and related academic literature. The results show that Indonesia has taken significant steps, especially in reducing deforestation, despite facing challenges such as international politics and diverse domestic interests. A strong commitment from Indonesia in implementing the Glasgow Pact is important to maintain environmental sustainability, reduce carbon emissions, and increase resilience to future climate change impacts.